2008 5th International Symposium on Turbo Codes and Related Topics 2008
DOI: 10.1109/turbocoding.2008.4658664
|View full text |Cite
|
Sign up to set email alerts
|

Upper bounds on the MAP threshold of iterative decoding systems with erasure noise

Abstract: Abstract-Following the work of Méasson, Montanari, and Urbanke, this paper considers the maximum a posteriori (MAP) decoding thresholds of three iterative decoding systems. First, irregular repeat-accumulate (IRA) and accumulate-repeat-accumulate (ARA) code ensembles are analyzed on the binary erasure channel (BEC). Next, the joint iterative decoding of LDPC codes is studied on the dicode erasure channel (DEC). The DEC is a two-state intersymbol-interference (ISI) channel with erasure noise, and it is the simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For simplicity of notation, we drop S 0 in all the expressions although the dependency on S 0 is always implied. From (26) and (27), it is clear that…”
Section: A Gexit Curves For the Isi Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity of notation, we drop S 0 in all the expressions although the dependency on S 0 is always implied. From (26) and (27), it is clear that…”
Section: A Gexit Curves For the Isi Channelsmentioning
confidence: 99%
“…where x is the DE FP at channel erasure rate and y = y(x). The formula (14) for the DEC case is equivalent to the result shown in [26] by analyzing the BCJR algorithm.…”
Section: A Bp and Ebp Curves For The Gecmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to single user channels, the area theorem for the joint decoder can be used to compute an upper bound on the MAP threshold of the joint decoder. For example, this technique was applied to the joint decoding of a finite-state channel and an LDPC code in [12]. It has been observed that this upper bound is tight for regular LDPC ensembles transmitted over the BEC [13].…”
Section: Density Evolution and (G)exit Curvesmentioning
confidence: 99%
“…It is also demonstrated that the upper bound can be used to derive new capacity results, such as the dicode erasure channel (DEC). The DEC is a quantized version of the known dicode channel with additive white Gaussian noise (AWGN), which was studied in [13], [14]. DP-based simulations for this channel show that the optimal policy only visits a small (i.e., finite) subset of the state space and the actions associated with those states are unconstrained.…”
Section: Introductionmentioning
confidence: 99%